PERTANGGUNGJAWABAN NOTARIS TERKAIT PENOLAKAN PEMBUATAN AKTA SYARIAH DAN AKIBAT HUKUMNYA MENURUT SISTEM HUKUM DI INDONESIA. - Fadillah, Mohammad Ari; Kencanawati, Erny; Halim, Anriz Nazaruddin (SENTRI: Jurnal Riset Ilmiah, 2024)
The refusal of notaries to make Sharia deeds without a valid reason raises important issues regarding their legal liability and its legal consequences in the Indonesian legal system. Although the law provides for the obligation of notaries to act fairly and non-discriminatively, the existing legal literature is lacking in exploring the administrative, civil, and criminal legal implications of such refusal. This study raises two problems, namely how the legal consequences for notaries related to the rejection of making Sharia deeds according to the legal system in Indonesia and how the responsibility of Notaries related to the rejection of making Sharia deeds according to the legal system in Indonesia, using the theory of legal consequences and liability theory of Hans Kelsen. The method used in this study is the normative juridical method, namely legal research conducted by researching library materials or secondary data only. The research approach used is the approach of legislation, case approach, analytical approach and conceptual approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, researching library materials (books, scientific journals, research reports) and other sources of legal materials that are relevant to the legal issues under study. For technical analysis of legal material is done by systematic and grammatical interpretation. The results of this study that the reason noltaris mellnollak mellrellsmikan kolnvellnsiolnal deed is karellna ulrulsan religious law. The choice undertaken Noltaris only mellrellsmikan deed that bellrsifat Sharia karellna call ulntulk tulndulk heart and patulh tellrhadap kellimanan principle that he lived. It tellrsellbult, based ollellh pellrintah in Al-Qulran and Al-Hadith, “Rasullulllah sallallahul ' alaihi wa sallam mellaknat pellmakan riba (rellntellnir), pellnyelltolr riba (customers who mellminjam), pellnullis riba transactions (sellkrelltaris) and Dula witness mellnyaksikan riba transactions, sellmulanya same dalamSS dolsa.” (HR. Mulslim Zero. 1598Noltaris the mellnollak mellrellsmikan kolnvellnsiolnal deed in pellservice pulblik mellrulpakan sulatul rights owned by noltaris sellbagai nellgara citizens, where nellgara is obliged to ulntulk mellngakolmoldasi the rights of bellrnellgara from seaeach country citizen